2020
DOI: 10.3389/fpsyt.2020.567394
|View full text |Cite
|
Sign up to set email alerts
|

Balance Problems, Paralysis, and Angina as Clinical Markers for Severity in Major Depression

Abstract: Major depressive disorder (MDD) is a heterogeneous disorder. Our hypothesis is that neurological symptoms correlate with the severity of MDD symptoms. One hundred eighty-four outpatients with MDD completed a self-report questionnaire on past and present medical history. Patients were divided into three roughly equal depression severity levels based on scores from the APA Severity Measure for Depression—Adult (n = 66, 58, 60, for low, medium, high severity, respectively). We saw a significant and gradual increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Later studies on MSA patients also found similar results with the finding that MSA patients with longer disease duration and severer disease conditions tended to have a worse psychiatric status, especially regarding depression ( 75 , 80 ). Prior studies have also reported those two characteristics as potential risk factors contributing to the increased severity of depression observed among patients with other neurodegenerative diseases ( 97 ). To summarize, it is reasonable to propose that MSA patients, especially female patients and those with longer disease duration and severer disease conditions may be more likely to suffer from depression.…”
Section: Clinical Features Of Msa-related Depressionmentioning
confidence: 94%
“…Later studies on MSA patients also found similar results with the finding that MSA patients with longer disease duration and severer disease conditions tended to have a worse psychiatric status, especially regarding depression ( 75 , 80 ). Prior studies have also reported those two characteristics as potential risk factors contributing to the increased severity of depression observed among patients with other neurodegenerative diseases ( 97 ). To summarize, it is reasonable to propose that MSA patients, especially female patients and those with longer disease duration and severer disease conditions may be more likely to suffer from depression.…”
Section: Clinical Features Of Msa-related Depressionmentioning
confidence: 94%
“…For item 8, as poor balance is associated with depressive symptoms, we focused on developing user’s balance and proprioceptive neuromuscular system. Qi and colleagues [ 56 ] showed that muscular paralysis and balance problems were significantly associated with increased severities of depression (odds ratio 13.5 and 2.9, respectively), and recommended that testing for changes in balance and muscular paralysis could be useful biomarkers for assessing depression severity that could be administered regularly for monitoring patients with major depressive disorders [ 56 ]. Similarly, the “gait and brain study” showed that depressive symptoms may amplify balance problems in older adults with mild cognitive impairment during sensorimotor challenges [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some shortcomings in this study should be mentioned here: (i) the number of included participants was relatively small, which made our findings needing future studies to validate further and support ( 34 , 35 ); (ii) all of the included BPPV and VM patients were from the same place, which could limit the applicability of our results; (iii) we only explored the sleep disorders of two kinds of neuropsychiatric disorders; neurotologists should further investigate the sleep problems of patients with other neuropsychiatric disorders, such as depression ( 36 38 ); (iv) sex and age were two mainly confounding factors in life science researches ( 39 41 ). In this study, limited by the relatively small sample size, we did not analyze whether there were sex- or age-specific sleep disorders in patients with VM or BPPV; this point was worthy of further investigations.…”
Section: Limitationsmentioning
confidence: 98%